Liquidity in People's Credit Banks: NPL and Operational Costs in Sidoarjo, Indonesia: Dampak Non-Performing Loan dan Biaya Operasional terhadap Likuiditas Bank Perkreditan Rakyat Konvensional: Studi di Sidoarjo, Indonesia. - Isnaini; Nihlatul Qudus Sukma Nirwana (Academia Open, 2024)
This study aimed to investigate the effect of Non-Performing Loan and Operational Costs on the liquidity of conventional People's Credit Banks in Sidoarjo, Indonesia. The study used a quantitative research method with a multiple regression analysis processed using SPSS version 23. The sample consisted of 35 People's Credit Banks out of 59 registered in the Otoritas Jasa Keuangan during the 2020 period. The results showed that Non-Performing Loan and Operational Costs did not have a partial effect on liquidity, but they had a simultaneous effect on liquidity. Highlights: The study focuses on the impact of Non-Performing Loan and Operational Costs on liquidity in People's Credit Banks in Sidoarjo, Indonesia. Quantitative research method and multiple regression analysis using SPSS version 23 were employed for data analysis. Findings indicate a simultaneous effect of Non-Performing Loan and Operational Costs on liquidity in these banks. Keywords: Non-Performing Loan, Operational Costs, Liquidity, People's Credit Banks, Indonesia